ANALISIS PENGARUH KUALITAS PELAPORAN KEUANGAN DAN MATURITAS UTANG TERHADAP EFISIENSI INVESTASI (Studi Kasus Pada Perusahaan Pertambangan Go Public yang terdaftar di Bursa Efek Indonesia Tahun 2017-2019) - lindary, Whilma; Mubyarto, Novi; Zahara , Anzu Elvia (Manajemen Keuangan Syariah, 2022)
The purpose of this research is to see how financial reporting quality and debt maturity affect investment efficiency.This research used a sample of publicly traded companies that were listed on the Indonesia Stock Exchange from 2017 to 2019.There are 17 companies that meet the criteria based on the purposive sampling method.The model Common Effect was chosen for this analysis using panel data regression analysis.These results show that the quality of financial reporting and debt maturity have a significant impact on the investment efficiency in mining companies publicly traded on the Indonesia Stock Exchange from 2017 to 2019.